2007
DOI: 10.1002/path.2181
|View full text |Cite
|
Sign up to set email alerts
|

Signet ring cell differentiation in mucinous colorectal carcinoma

Abstract: Approximately 10% of all colorectal carcinomas are mucinous carcinomas, characterized by extracellular mucin. Occasionally, mucin accumulates intracellularly in these tumours, causing signet ring cell differentiation. We hypothesized that signet ring cells arise from a separate genetic pathway. In this study the molecular background of signet ring cell differentiation was investigated by analysing genetic changes, changes in the expression of adhesion molecules, and mucin content. Furthermore, its clinical rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 30 publications
8
75
0
8
Order By: Relevance
“…The negative prognostic effect of MA becomes more readily apparent when the adverse effects are minimal in the low-risk group. In accordance with the molecular background, low expression of the adhesion molecules, such as E-cadherin and β-catenin may result in reduced cell adhesion in regions of high mucinous content and may promote scattering of cancer cells, further leading to local recurrence, distant metastasis and poor prognosis [25,26]. These findings are supported by another cohort [27] in which a preponderance of local relapse was observed.…”
Section: Discussionsupporting
confidence: 75%
“…The negative prognostic effect of MA becomes more readily apparent when the adverse effects are minimal in the low-risk group. In accordance with the molecular background, low expression of the adhesion molecules, such as E-cadherin and β-catenin may result in reduced cell adhesion in regions of high mucinous content and may promote scattering of cancer cells, further leading to local recurrence, distant metastasis and poor prognosis [25,26]. These findings are supported by another cohort [27] in which a preponderance of local relapse was observed.…”
Section: Discussionsupporting
confidence: 75%
“…We failed to detect increased ALK expression by IHC in any of the 42 cases tested in this study, including the single case that was positive by FISH. The failure to show ALK overexpression in the FISH positive case could be due to the discohesive nature of signet ring cancers leading to relatively scanty amount of cellular material against a broad infiltrative stroma [Borger et al 2007]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the signet-ring cell component was not an independent predictor of poor outcome in multivariate analysis of mucinous adenocarcinoma. Borger et al 14 reported that the presence of signet-ring cells in mucinous adenocarcinoma correlated with increased T-stage and poor prognosis and these cells showed disruption of the E-cadherin/b-catenin complex. Signetring cells are usually present as single cells or in loose clusters, which implies a disruption in cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain their aggressive behavior with regard to invasion and metastasis. Borger et al 14 reported that the presence of signet-ring cells in mucinous adenocarcinoma correlated with increased T-stage and poor prognosis. In the current practice of pathology, there is no definitive rule on how to report a minor component of signet-ring cells in colorectal mucinous adenocarcinomas.…”
mentioning
confidence: 99%